Assessing the performance of the Caregiver Reported Early Development Instruments (CREDI) in rural India - Alderman, Harold; Friedman, Jed; Ganga, Paula; Kak, Mohini; Rubio‐Codina, Marta (New York Academy of Sciences, 2021)
Although many education and health programs aim to improve early childhood development, it is challenging to assess developmental levels of infants and small children through large household surveys. The Caregiver Reported Early Development Instruments (CREDI) has been proposed as an adaptable, practical, and low‐cost instrument for measuring the developmental status of children under 3 years of age at scale, as it is relatively short and collected by caregiver report. This study employed the CREDI to measure the development of a sample of 994 children ages 22–35 months in rural India and compared the results to those obtained using the Bayley Scales of Infant and Toddler Development (Bayley‐III), a reliable and widely used instrument, albeit one not always suited to large‐scale data collection efforts given its length, cost, and complexity of administration. The CREDI validation exercise showed that caregivers can provide assessments in keeping with the more interactive (hence more time‐consuming and training‐intensive) Bayley‐III instrument. Noteworthy, there was no indication that concordance of the instruments differed by education of the caregiver. This is important as it points to alternate feasible tools to measure child development outcomes through large‐scale surveys.